Towards sustainable urban development: the social acceptability of high-rise buildings in a Ghanaian city - Agyemang, Felix S. K.; Silva, Elisabete; Anokye, Prince Aboagye (GeoJournal, 2018)
Over the years, many city managers, policy makers and academics alike have turned to high-rise buildings as pathway to sustainable urban development. However, the sustainability of such types of development in various geographical contexts, especially in sub-Saharan Africa, is a subject less explored. Amidst the promotion of high-rise development in a rapidly urbanizing metropolis in Ghana, Kumasi, the research empirically examined the social acceptability of high-rise residential facilities and the institutional capacity for their effective management. By conducting face-to-face interviews with sampled households, and critical public service providers in the metropolis, the study uncovered that, contrary to the evidence from many Asian cities, there is generally low social acceptability of high-rise developments, and a weak institutional capacity for effective service delivery. The research concludes that, whilst it is tempting to embrace high-rise buildings as sustainable development pathway, it is crucial they are pursued with much circumspection. In addition to their design being tailored to the local needs of the people for whom they are built, the promotion of high-rise development should recognize the importance of effective service delivery, and general social acceptability.